The Effect of Health Promotion on Adolescents' Knowledge of Reproductive Health - Evi Sonjati; Gita Arisara; Dini Afriani; Tiara Khoirunnisa (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
Adolescence is a transition period between childhood and adulthood and has relatively not reached the stage of mental and social maturity so that they have to face conflicting emotional and social pressures.Reproductive health is a complete physical, mental, and social act. Health promotion is an effort made towards the community so that they are willing and able to maintain and improve their health. Knowledge is an important domain in the formation of open behavior. The purpose of the study was to determine the effect of health promotion on adolescents' knowledge about reproductive health at SMP 11 April Sumedang in 2024. This type of research is quantitative with Pre-Experimental designs research method, with the research design used One Group Pretest-Posttest. The sample collection technique used total sampling with a sample of 74 respondents. The measuring instrument used was a reproductive health knowledge questionnaire. The analysis used the Wilcoxon signed rank test. The results showed that there was an effect of health promotion on adolescents' knowledge about reproductive health at SMP 11 April Sumedang in 2024 with a p-value 0,000 (p < 0.05). Health promotion plays an important role in increasing adolescent knowledge about reproductive health.